Environmental Assessment and Cost Analysis of the Manufacturing, Transport, and Use of Actellic Super and Azadirachtin Insecticides for the Treatment of Maize Grains - Darfour, Bernard; Rosentrater, Kurt A. (Frontiers in Sustainable Food Systems, 2022)
The public has recommended the use of botanicals with insecticidal properties because of the environmental and human health hazards associated with the utilization of synthetic chemicals. Farmers and other stakeholders need to have optimal knowledge of the chemical treatment of grain. Also understanding how synthetic chemicals and botanicals impact the environment, and the cost involved in treating maize grain is important. Although some research had been done on Actellic Super and azadirachtin in other parts of the world based on different research goals, this study rather focused on peculiar assumptions, scope, goals, and system boundary. The objectives of this study were to evaluate the environmental impacts of the active ingredients in Actellic Super (pirimiphos-methyl and permethrin) and NeemAzal (azadirachtin), and also to perform cost analysis on the usage of Actellic Super and azadirachtin for the treatment of maize grain. Data from Sustainable Minds database and TRACI database were used to assess CO2 emissions and impacts of pirimiphos-methyl and permethrin during manufacturing and transport. Also, the ecotoxicity and health impacts of azadirachtin, pirimiphos-methyl, and permethrin were assessed. A unit of Ghana cedi per kilogram of grain was used for the cost analysis. Pirimiphos-methyl manufacturing recorded the lowest CO2eq. kg/kg emissions and impacts (mPts/kg) compared with permethrin. Air transport of pirimiphos-methyl and permethrin resulted in higher CO2eq. kg/kg emissions and impacts unlike sea transport. Pirimiphos-methyl recorded the highest ecotoxicity while the least was permethrin. Importantly, azadirachtin had no human health impacts compared with pirimiphos-methyl. Actellic Super costs 224% less compared with azadirachtin. However, the costs of both insecticides depended on foreign exchange rate. The treatment cost increased with grain capacity irrespective of the insecticide used. Although treatment cost increased with grain capacity, the economies of scale favored the largest grain capacity.